PERBEDAAN PROPRIOCEPTIVE NEUROMUSCULAR FACILITATION (PNF) STRETCHING DAN ICE MASSAGE DALAM MENCEGAH TERJADINYA DELAYED ONSET MUSCLE SORENESS (DOMS) PADA REMAJA DI DENPASAR - Made Wahyu Cahyadi; Ni Wayan Tianing; I Made Krisna Dinata (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT The purpose of this study was to determine the aim of this research the difference between proprioceptive neuromuscular facilitation (PNF) stretching and ice massage in preventing the occurrence of delayset onset muscle soreness (DOMS). This research is an experimental study with post test two group desaign and using simple random sampling technique. The sample of the study were 20 male students selected based on the inclusion and exclusion criteria, which were then divided into two groups. Group 1 was given treatment of pnf stretching and group 2 was given ice massage treatment. DOMS pain was measured using visual analogue scale (VAS) at 48 h after treatment. Hypothesis test of this research using Mann-Whitney U-test, where got result p = 0,027 (p <0,05). These results show that there is a significant difference between pnf stretching and ice massage. Mean of DOMS pain value in group 1 was 2,560 and mean of DOMS pain value in group 2 was 1,200. This shows that ice massage group results in lower DOMS pain value compared to pnf stretching group. Based on the results of this study, it is concluded that ice massage is better than pnf stretching in preventing DOMS. Keyword: delayet onset muscle soreness (DOMS), PNF Stretching, Ice Massage, visual analogue scale (VAS)